SEJARAH PEMEKARAN KABUPATEN TEBO PROVINSI JAMBI (1999-2015) - Kevin Reza; Kamaruddin Oemar; Tugiman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The institution of a certain administration of an area is always needed in order to achieve good governance and provide services for people’s welfare in accordance with the ability of each area for its growth and development process. Every region in the world has its own history in terms of the establishment process, area naming and the development of the area which make it unique. This also happened in Tebo Regency in Jambi Province, which is an area that instituted in the reformation period. The purpose of this research is to discover the division history of Tebo regency, to know past trips Tebo Regency before it become regency in 1999, to know background the division of Tebo Regency, to know early condition after becoming regency and to know supporting and hindering factors of the division process Tebo Regency in Jambi Province. The method used in this research is the historical method, where data were collected through observation, interviews, literature study and documentation. Data analysis used in this research is descriptive analysis. The location of the research is in Tebo Regency in Province Jambi. The time of research is spanned from the proposal seminar up to thesis seminar. The results show Tebo Regency has a long history background. The area has occupied before The Dutch colony entered this area. In 1906 The Dutch colony began to set the it to be Afdeeling area of Dutch East Indies Government. The division process of Tebo Regency got positive response from local government and received a magnitude of public aspiration for institution of Tebo area to be regency. The processes finally get the results with the enactment law No. 54 of 1999 about formation of Sarolangun Regency, Tebo Regency, Muaro Jambi Regency and East Tanjung Jabung Regency. Tebo Regency was officially born in 12 October 1999. Key Words : History, Tebo Regency, Division